Microplanning workshops for high-quality vaccination in Brazil: an experience report, 2023 - Ana Catarina de Melo Araújo; Luciana Maiara Diogo Nascimento; Carla Conceição Ferraz; Elice Eliane Nobre Ribeiro; Fernanda Penido Matozinhos; Eder Gatti Fernandes (Epidemiologia e Serviços de Saúde, 2024)
ABSTRACT Objective To report the experience of workshops designed for action plans in microplanning vaccination in Brazilian states and municipalities. Methods This was a report on microplanning workshops aimed at mapping the local population, target population and identifying appropriate and effective vaccination actions. Vaccination actions were planned according to the reality of the municipalities using the microplanning method for high-quality vaccination activities. Results The workshops aimed at establishing effective vaccination strategies were held between July 15 (Macapá, capital city of Amapá state) and September 14, 2023 (Belo Horizonte, capital city of the state of Minas Gerais), with a total of 1,232 participants, including surveillance technicians, primary care and other health sectors. The diversity of participants highlighted distinct challenges and the importance of cooperation in addressing low vaccination coverage across the country. Conclusion The workshops served as a platform for raising awareness and exchanging experiences among stakeholders involved in vaccination.